2010
DOI: 10.3346/jkms.2010.25.10.1449
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pRb, p53, p16 and Cyclin D1 and Their Clinical Implications in Urothelial Carcinoma

Abstract: The aim of this study was to assess immunohistochemical expression of p53, pRb, p16, and cyclin D1, alone or in combination, as prognostic indicators and to investigate their correlation with clinocopathologic features of urothelial carcinoma. Immunohistochemical staining for p53, pRb, p16, and cyclin D1 was performed on a tissue microarray from 103 patients with urothelial carcinoma who underwent radical cystectomy. Of the patient samples analyzed, 36 (35%), 61 (59%), 47 (46%) and 30 (29%) had altered express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
(33 reference statements)
1
15
1
Order By: Relevance
“…Olsson et al [23] also used the same staining pattern (p16d) in stage T1 urinary bladder cancers and they detected normal p16 expression was related to a lower risk of tumor progression. Similar to our study, Lee et al [21] investigated four cell cycle proteins (p16, pRb, p53, cyclin D1) and found no correlation between progression and p16 (p16d method) expression; their results suggested that multiple genetic defects affected the clinical course and metastatic capacity of bladder carcinomas. Shariat et al used the staining pattern of p16d and they determined that combined staining of p16 and pRb can be a useful marker in prognosis of bladder cancer [22].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Olsson et al [23] also used the same staining pattern (p16d) in stage T1 urinary bladder cancers and they detected normal p16 expression was related to a lower risk of tumor progression. Similar to our study, Lee et al [21] investigated four cell cycle proteins (p16, pRb, p53, cyclin D1) and found no correlation between progression and p16 (p16d method) expression; their results suggested that multiple genetic defects affected the clinical course and metastatic capacity of bladder carcinomas. Shariat et al used the staining pattern of p16d and they determined that combined staining of p16 and pRb can be a useful marker in prognosis of bladder cancer [22].…”
Section: Discussionsupporting
confidence: 58%
“…Another study interpreted p16 expression below 5% as negative staining for p16 [1]. Some authors regarded expression loss (no staining) and overexpression (staining > 50%) as abnormal and moderate staining as normal [21][22][23][24]. Four of the scoring methods employed in these studies were also used in our work for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…TUG1 may be an important factor in the p53-regulatory network; p53 is a tumor suppressor gene, the mutation of which is associated with the occurrence and progression of numerous cancer types, including those of the liver (26), breast (27), bladder (28) and stomach (29). As reported, p53 may also serve an important function in the occurrence and development of brain glioma (30).…”
Section: Discussionmentioning
confidence: 99%
“…For further statistical analysis, all markers were assigned to one of two categories: normal (wild type) or abnormal (altered). The cut-off values were chosen from the studies in the literature and are summarized in Table 1 [11, 12, 18, 20–24]. …”
Section: Methodsmentioning
confidence: 99%